Public key cryptosystem based on algebraic geometric codes - ZHANG Ying; YUE Dian-wu (Tongxin xuebao)
A public-key cryptosystem based on algebraic geometric codes was proposed.The cryptosystem is a pub-lic-key system combined with error correcting.Compared with M public-key system and some variants,the performance of the public-key cryptosystem was analyzed.It is shown that the security,information rate,error correcting,and prob-ability of correct decipher were improved.